Hyers–Ulam Stability of Additive Functional Equation Using Direct and Fixed-Point Methods. (14th December 2020) - Tamilvanan, K.; Balasubramanian, G.; Alessa, Nazek; Loganathan, K.
Abstract : In this present work, we obtain the solution of the generalized additive functional equation and also establish Hyers–Ulam stability results by using alternative fixed point for a generalized additive functional equation χ ∑ g = 1 l v g = ∑ 1 ≤ g < h < i ≤ l χ v g + v h + v i − ∑ 1 ≤ g < h ≤ l χ v g + v h − l 2 − 5 l + 2 / 2 ∑ g = 1 l χ v g − χ − v g / 2 . where l is a nonnegative integer with ℕ − 0, 1, 2, 3, 4 in Banach spaces.